2021
DOI: 10.3390/md19010033
|View full text |Cite
|
Sign up to set email alerts
|

A Microencapsulation Method for Delivering Tetrodotoxin to Bivalves to Investigate Uptake and Accumulation

Abstract: Most marine biotoxins are produced by microalgae. The neurotoxin tetrodotoxin (TTX) has been reported in many seafood species worldwide but its source is unknown, making accumulation and depuration studies in shellfish difficult. Tetrodotoxin is a water-soluble toxin and cannot be directly ingested by shellfish. In the present study, a method was developed which involved binding TTX to solid particles of humic acid and encapsulating them in agar-gelatin capsules. A controlled quantity of TTX-containing microca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…This result indicates that this species has a physiological mechanism for the accumulation of TTX in the body from outside the body, which would be one piece of evidence supporting the exogenous nature of TTX in this species. Similarly, orally administered TTX can accumulate in the body of the tiger puffer T. pardalis within 24 h (Gao et al 2019) and the bivalve Paphies australis within 7-13 days (Biessy et al 2021). By contrast, despite the administration of TTX, TTX levels in the arms of individuals exposed to predators decreased by about 30% in 3 days (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…This result indicates that this species has a physiological mechanism for the accumulation of TTX in the body from outside the body, which would be one piece of evidence supporting the exogenous nature of TTX in this species. Similarly, orally administered TTX can accumulate in the body of the tiger puffer T. pardalis within 24 h (Gao et al 2019) and the bivalve Paphies australis within 7-13 days (Biessy et al 2021). By contrast, despite the administration of TTX, TTX levels in the arms of individuals exposed to predators decreased by about 30% in 3 days (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…Few data are available in the literature about TTX distribution in mollusk tissues. Vlamis et al [34] found similar levels in the DG and WF (202.9 and 179.1 µg TTX kg −1 , respectively) of Greek mussels, while Biessy et al [46][47][48] reported preferential accumulation of TTXs in siphons and DG in clam species from New Zealand (Paphies australis). Rapkova et al [49] found the highest TTX levels in the DG of Pacific oysters (Crassostrea gigas) harvested from a production area in southern England.…”
Section: Discussionmentioning
confidence: 97%
“…Accumulation in the DG could indicate dietary TTX uptake, while a more homogeneous distribution in the mollusk tissues could be the result of contamination from symbiotic microorganisms. However, it has also been demonstrated that after ingestion and accumulation in the DG, TTXs can migrate from one tissue compartment to another in bivalve mollusks [47]. High toxin accumulation in DG can thus provide evidence for recent or ongoing TTX contamination.…”
Section: Discussionmentioning
confidence: 99%
“…Biessy et al. (2021) fed specimens of P. australis with solid microcapsules containing TTX and monitored toxin accumulation within the bivalves. Even though the toxin intake during each feeding was very low (0.5%–1% of TTX), concentrations reached up to 103 µg/kg just 2 weeks after the treatments.…”
Section: Ttx Presence In Live Bivalve Mollusks and Causative Factors ...mentioning
confidence: 99%
“…Interestingly, two studies have also investigated the uptake of TTXs in bivalve mollusks, to better shed light on possible accumulation rates and to understand possible accumulation routes thorough the food chain. Biessy et al (2021) fed specimens of P. australis with solid microcapsules containing TTX and monitored toxin accumulation within the bivalves. Even though the toxin intake during each feeding was very low (0.5%-1% of TTX), concentrations reached up to 103 µg/kg just 2 weeks after the treatments.…”
Section: Ttx Presence In Live Bivalve Mollusks and Causative Factors ...mentioning
confidence: 99%